The Role of Fines in Punishment: Historical Origins, Legal Regulation and Comparative Judicial Practice - Jadamba, Baasanjav; Gal, Tuya (Advances in Social Sciences Research Journal, 2025)
Our study examines the historical development, legal foundations, and comparative judicial application of fines in the United States, Germany and Japan. It highlights significant structural differences between fine systems—particularly between Germany’s income-based day-fine model and the rigid statutory framework in post-socialist and identifies persistent tensions between the deterrent purpose of fines and their disproportionate impact on economically vulnerable offenders. The study concludes that reforms such as income-sensitive fine calculation, non-custodial enforcement mechanisms, and stronger judicial capacity for proportional sentencing are essential to align monetary penalties with core principles of criminal justice.